Peripheral Arterial Disease Is Prevalent But Underdiagnosed and Undertreated in the Primary Care Setting in Central Greece. (February 2013) - Argyriou, Christos; Saleptsis, Vasileios; Koutsias, Stylianos; Giannoukas, Athanasios D.
We investigated the prevalence of peripheral arterial disease (PAD). Primary Care Health Centers (n = 14) in Thessaly (central Greece) recruited 436 participants, mean age 71 (50-79) years. Peripheral arterial disease was considered present if the ankle–brachial index (ABI) was <0.9 or >1.4 in at least 1 leg. Asymptomatic PAD was defined as an abnormal ABI and no symptoms or history of limb revascularization. The prevalence of PAD was 13% (mostly asymptomatic, 11.7%). Only 5 (8.77%) of 57 patients with PAD were aware of their disease and only in these patients were the physicians aware of the presence of PAD. The risk factors associated with PAD were age, smoking, and the combination of diabetes mellitus and coronary artery disease. All symptomatic patients were on antiplatelet therapy but 33% did not take statins. For asymptomatic patients, 74.5% were not on antiplatelet therapy and 57% did not receive statins. In the primary health care setting, PAD is underdiagnosed and undertreated.